Review of the Potential Effects of Semaglutide and Metformin in the Management of Polycystic Ovary Syndrome (PCOS) and Obesity - Kaur, Prabhleen; Solanki, Raj; Manocha, Nimita; Gautam, Rupesh K; Chopra, Hitesh (Scripta Medica, 2025)
Polycystic ovary syndrome (PCOS) is considered a lifestyle disorder. Various lifestyle factors hinder obesity and insulin resistance, which worsen the symptoms of PCOS and this makes existing treatment very challenging. This review examines 10 studies on the effectiveness of combining glucagon-like peptide-1 (GLP-1) receptor agonists, particularly liraglutide and semaglutide, with metformin for weight control in women with PCOS. Results declared that combined therapy gives greater effects in terms of weight loss and metabolic improvement. Combined liraglutide with metformin led to an average weight reduction of 6.5 ± 29.55 kg and side-by-side reductions in body mass index (BMI), fasting glucose and insulin levels over 12 weeks. While comparing the monotherapy of metformin and liraglutide, liraglutide was more effective for weight loss, but the combination is thought to be impactful. Semaglutide monotherapy also emerged as a strong alternative, achieving a 9 kg weight reduction within 12 weeks in obese PCOS patients and was well-tolerated with minimal side effects. These findings suggest that combining semaglutide with metformin may be an effective approach for weight and metabolic issues in PCOS women, with semaglutide offering additional promise. Further studies are encouraged to refine dosing and explore long-term benefits.
Keywords: Polycystic ovary syndrome; Obesity; Glucagon-like peptide-1 receptor agonists; Semaglutide; Liraglutide; Metformin